2023
DOI: 10.1088/1741-2552/acab32
|View full text |Cite
|
Sign up to set email alerts
|

Neural evidence for functional roles of tactile and visual feedback in the application of myoelectric prosthesis

Abstract: Abstract. Objective. The primary purpose of this study was to investigate the electrophysiological mechanism underlying different modalities of sensory feedback and multi-sensory integration in typical prosthesis control tasks. Approach. We recruited 15 subjects and developed a closed-loop setup for three prosthesis control tasks which covered typical activities in the practical prosthesis application, i.e., prosthesis finger position control (PFPC), grasping force control (GFC) and box and block control (BABC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
(62 reference statements)
0
2
0
Order By: Relevance
“…However, multiple decision making complexities are involved within the human body to perform these tasks. The complexities include decision making for the type of gesture required to grasp the object, the selection of the grip force and feedback information from the sensory system of the hand and the visual sensory system of the eyes [ [1] , [2] , [3] , [4] ]. The decoding of the different muscle and brain signals has resulted in the designing of bionic devices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, multiple decision making complexities are involved within the human body to perform these tasks. The complexities include decision making for the type of gesture required to grasp the object, the selection of the grip force and feedback information from the sensory system of the hand and the visual sensory system of the eyes [ [1] , [2] , [3] , [4] ]. The decoding of the different muscle and brain signals has resulted in the designing of bionic devices.…”
Section: Introductionmentioning
confidence: 99%
“…Any error in the force prediction may result in the slippage of the object or breakage of the object. The neurophysiological studies have shown the complexities and changes in the somatosensory system, related to the skin [ 4 , 7 , 20 , 21 ]. These studies have shown that a human hand possesses a strong feedback system to manipulate the force while grasping an object [ 20 ].…”
Section: Introductionmentioning
confidence: 99%